Analisis Keberlanjutan Daya Dukung Lingkungan Melalui Kearifan Lokal Mulung di Pulau Lapang-Batang, Kecamatan Pantar Barat, Kabupaten Alor, Provinsi Nusa Tenggara Timur - Taufik Hidayat A. Putra Senin; Sukadari Sukadari (UM Purwokerto Press, 2023)
The writing of this article aims to: (1). Sustainability of the carrying capacity of the environment through Mulung local wisdom on Lapang-Batang Island; (2). Efforts to maintain Mulung local wisdom from the development of the tourism industry; (3). Supporting and inhibiting factors for the sustainability of environmental carrying capacity through Mulung local wisdom. The type of qualitative research used in this research is a case study, in which the researcher raises the phenomenon of the sustainability of the carrying capacity of the environment through Mulung local wisdom. Data collection techniques in this study were participatory observation, interviews, documentation and document studies. Data analysis techniques in this study used interactive models from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions.The results of the research show that the implementation of Mulung local wisdom is very beneficial for nature and humans and can prevent damage to nature from destructive efforts. The availability of biological natural resources in the waters of Lapang-Batang Island has an effect on increasing the economic aspect and the availability of jobs. The territorial waters of Lapang-Batang Island which are included in the customary territory of the Baranusa family have been registered with the Customary Territory Registration Agency which gives authority to the customary institutions of the Baranusa family to manage and preserve nature for the welfare of the community. Expansion of capitalism becomes a threat and challenge externally in an effort to maintain natural sustainability with local wisdom.